0013 Simulation to train psychiatric nurses for leadership. (2nd November 2015) - Campbell, Lloyd; Tritschler, Christina; Cross, Sean
Abstract : Background/context: The Duty Senior Nurse (DSN) role in South London and Maudsley NHS Foundation Trust (SLaM) has hitherto been an under-supported and somewhat nebulous one. Anecdotally many DSN's have craved more clarity and a forum to reflect with peers. Existing training for this group is primarily didactic in nature with little accommodation of reflective practice or experiential learning indicated as key to optimal learning. 1 Our team's recent work has indicated potential for simulation in a mental health setting, a novel application of the modality. A DSN course was developed to allow learners to explore their own and colleagues' practice, to recognise the impact of related non-technical skills, to identify personal and practical alternative behaviours and areas for improvement in providing safe, therapeutic services. Methodology/description: The three-day course was delivered on three occasions. It consisted of thirteen scenarios, each followed by a debrief. Iterative design was implemented whereby feedback from each course contributed to the next. Participants (n = 34) were senior nurses who responded as Leader to emergency calls in inpatient settings. Scenarios included: managing agitation, relatives/carers, seclusion, staff conflict, medical deteriorations, section 136, infection control and business continuity. Each was followed by a structured debrief. Results/outcomes: Feedback was very positive. Over 97% of participants agreed the program was useful and relevant to them, with 100% stating that they would recommend the course to a colleague. Most respondents identified specific lessons learned and changes they could apply to their own practice. In addition, a pre/post measure of confidence, knowledge and attitudes regarding the DSN role showed significant increases in most dimensions. Potential impact: Further research will be conducted on the course as it is implemented on a larger scale, but initial results indicate potential for simulation to be a valuable tool to aid the development of psychiatric nurses in mental health settings. Reference: Rudolph J, Simon R, Raemer D, Eppich W. Debriefing as formative assessment: Closing performance gaps in medical education. Acad Emerg Med 2008;15(11):1010–1016